The effect of nostalgia on self-continuity, pride, and intention to visit a sport team's hometown. Issue 2 (3rd July 2019) - Chang, Mark Jaewon; Schneider, Robert C.; Connaughton, Daniel P.; Hager, Peter F.; Ju, Ilyoung
ABSTRACT: The primary purpose of the current study was to develop a theoretical model regarding nostalgia, self-continuity, pride, and the intention to visit a sport team's hometown and examine the moderating effect of length of time as a sport fan. The study involved showing a short nostalgic video clip and investigated relationships using structural equation modeling (SEM) and multigroup SEM. The results suggest that self-continuity is an important indicator of the relationship between nostalgia and pride and enhances the intention to visit a sport team's hometown. The results also showed that self-continuity is an important indicator for new fans but not for long-term fans.